Increased host investment in extrafloral nectar (EFN) improves the efficiency of a mutualistic defensive service. - Marcia González-Teuber; Juan Carlos Silva Bueno; Martin Heil; Wilhelm Boland (PLoS ONE, 2012)
Extrafloral nectar (EFN) plays an important role as plant indirect defence through the attraction of defending ants. Like all rewards produced in the context of a mutualism, however, EFN is in danger of being exploited by non-ant consumers that do not defend the plant against herbivores. Here we asked whether plants, by investing more in EFN, can improve their indirect defence, or rather increase the risk of losing this investment to EFN thieves. We used the obligate plant-ant Acacia-Pseudomyrmex system and examined experimentally in the field during the dry and the rainy seasons how variations in EFN secretion are related to (i) ant activity, to (ii) the ant-mediated defence against herbivores and (iii) the exploitation of EFN by non-ant consumers. Extrafloral investment enhanced ant recruitment and was positively related to the ant mediated defence against herbivores. The ant-mediated protection from exploiters also increased in proportion to the nectar sugar concentration. Although the daily peak of EFN production coincided with the highest activity of EFN thieves, Pseudomyrmex ferrugineus ants protected this resource effectively from exploiters. Nevertheless, the defensive effects by ants differed among seasons. During the dry season, plants grew slower and secreted more EFN than in the rainy season, and thus, experienced a higher level of ant-mediated indirect defence. Our results show that an increased plant investment in an indirect defence trait can improve the resulting defensive service against both herbivores and exploiters. EFN secretion by obligate ant-plants represents a defensive trait for which the level of investment correlates positively with the beneficial effects obtained.